Tingkat Penyesuaian Sosial Anak Asuh di Panti Asuhan Wira Lisna - Imalatul Khairat; Peni Ramanda; Yogi Damai Syaputra (Universitas Mathla'ul Anwar Banten, 2021)
THE LEVEL OF SOCIAL ADJUSTMENT OF FOSTER CHILDREN AT THE WIRA LISNA ORPHANAGE. This study aims to reveal the conditions of social adjustment of foster children in the orphanage. This research uses quantitative methods. The data were collected through a social adjustment scale that the author developed himself with a reliability of 0.936. The sample of this research is 10 foster children at the Wira Lisna orphanage in the city of Padang. The data analysis used in this research is descriptive statistics. The results of this study reveal that the level of social adjustment of Wira Lisna Padang's anti-care foster children is in the unfavorable category. The results of this study can be used as a basis for determining the next step in order to improve the social adjustment ability of foster children at the Wira Lisna orphanage, Padang. The intervention efforts provided can be tailored to the researcher's area of expertise.